(untitled) (Research, Society and Development, 2021)
Deep vein thrombosis is a disease that affects millions of people around the world every year, there are predispositions to this disease in both sexes such as smoking, genetic conditions and factors related to lifestyle. However, for females there is an agent of constant and very frequent exposure, which is oral contraceptives, these drugs are used to prevent pregnancy, and in some cases to treat diseases of hormonal nature and that affect only women. It is described in the literature that oral contraceptives cause these risks because they are composed of synthetic hormones such as progesterone and estrogen, and they affect blood clotting. This is a literature review in the Scielo, Google Scholar, Lilacs and BVS databases focusing on the correlations between contraceptive use and deep vein thrombosis, studying hemostasis and the pharmacological effects of oral contraceptive hormones in the coagulation cascade. It is concluded that contraceptive hormones can have an adverse effect on venous thrombosis, as the hormones used in their matter cause changes in the coagulation cascade and inhibit factors that help the body to avoid hypercoagulability.